Isolation of 3-(4-hydroxyphenyl)methylpropenoate and bioactivity evaluation of Gomphrena celosioides extracts - Dosumu, O. O.; Ekundayo, O.; Idowu, P. A.; Onocha, P. A. (Technische Universität Dortmund, 2011)
The efficacy of Gomphrena celosioides extracts in traditional medicine in the treatment of infectious diseases was evaluated by biological assays. The bioactivities of the extracts of this plant were tested against organisms. The ethyl acetate and methanol extracts of the plant displayed inhibition activities on Staphylococcus aureus, Bacillus subtilis, Pseudomonas aeruginosa, Escherichia coli and Salmonella typhi. Methanol extract was active against Candida albicans, Aspergillus niger and Trichophyton species with diameter zones of inhibition between 14 and 20 mm. Fractionation of the methanol extract produced 3-(4-hydroxyphenyl) ethylpropenoate with mild antimicrobial activity against the test microorganisms. The anthelmintic assay showed ethyl acetate and methanol extracts to be active against Fasciola gigantica, Taenia solium and Pheretima pasthuma. Ethyl acetate was the most toxic of the extracts causing paralysis of Taenia solium within 15 minutes and the death of Fasciola gigantica within 20 minutes of application. The brine shrimp assay gave an LC50 of 52.15 and 77.98 μg/ml on hexane and methanol extracts respectively. The result of this work corroborated the folkloric use of Gomphrena celosioides in the treatment of infectious diseases.
EXCLI Journal ; Vol. 9, 2010
Keywords: anthelmintic; antimicrobial; cytotoxicity; Gomphrena celosioides; phytochemical analysis; 610